Orthorhombic carbon oC24: A novel topological nodal line semimetal - Li, Zhen-Zhen; Chen, Jia; Nie, Simin; Xu, Lifang; Mizuseki, Hiroshi; Weng, Hongming; Wang, Jian-Tao (PERGAMON-ELSEVIER SCIENCE LTD, 2018)
We identify by ab initio calculations a stable three-dimensional carbon allotrope that constructed by inserting benzene rings into the carbon-carbon bonds in a previously reported oC8 carbon. This new carbon phase has a 24-atom orthorhombic unit cell in Cmmm (D-2H(19)) symmetry and thus termed oC24. Phonon mode analysis confirms its dynamical stable. Total-energy calculations show that it is energetically stable comparable with (5,5) carbon nanotube. Detailed electronic band calculations reveal that oC24 is a topological node-line semimetal with two mirror-inversion symmetric nodal lines that go through the whole Brillouin zone in bulk and a projected surface flat band around the Fermi level. The present results establish a new type of carbon phases and offer insights into their outstanding structural and electronic properties. (C) 2018 Elsevier Ltd. All rights reserved.
Keywords: ALLOTROPES; STABILITY; PHASES